Menerobos Batasan : Pendidikan Tanpa Batas Dengan Teknologi - Nya Abelia Fitri; Izatum Mufida; Nadia Ayu Wulandari; Dea Intan Nuraini; Nurul Mahruzah Yulia (Journal of Practice Learning and Educational Development, 2026)
The transformation of information and communication technology (ICT) has changed the paradigm of global education, enabling broader, more flexible, and inclusive access to learning. This study aims to analyze the role of technology in overcoming the limitations of conventional education in Indonesia, as well as evaluating the challenges and solutions in its implementation. Using literature study methods and descriptive analysis, this study examines various technological approaches such as online learning, mobile learning, and intelligent information systems. The results of the study show that technology plays a significant role in improving the accessibility and quality of education, although there are still challenges such as the digital divide and limited infrastructure. Collaboration is needed between the government, educational institutions, and the private sector to optimize the use of technology in education.